Customizably designed multibodies neutralize SARS-CoV-2 in a variant-insensitive manner - Abreu, Cecilia; Ortega, Claudia; Olivero-Deibe, Natalia; Carrión, Federico; Gaete-Argel, Aracelly; Valiente-Echeverría, Fernando; Soto-Rifo, Ricardo; Milan Bonotto, Rafaela; Marcello, Alessandro; Pantano, Sergio (Frontiers in Immunology, 2023)
The COVID-19 pandemic evolves constantly, requiring adaptable solutions to combat emerging SARS-CoV-2 variants. To address this, we created a pentameric scaffold based on a mammalian protein, which can be customized with up to 10 protein binding modules. This molecular scaffold spans roughly 20 nm and can simultaneously neutralize SARS-CoV-2 Spike proteins from one or multiple viral particles. Using only two different modules targeting the Spike's RBD domain, this construct outcompetes human antibodies from vaccinated individuals' serum and blocks in vitro cell attachment and pseudotyped virus entry. Additionally, the multibodies inhibit viral replication at low picomolar concentrations, regardless of the variant. This customizable multibody can be easily produced in procaryote systems, providing a new avenue for therapeutic development and detection devices and contributing to preparedness against rapidly evolving pathogens.